Institutionalization of the water-energy-food-environment nexus in the Niger Basin - Seidou, Ousmane; Ringler, Claudia; Kranefeld, Robert; Abdouramane, Gado Djibo; Traoré, Abdou Ramani; Ibraheem, Olomoda; Agossou, Gadedjisso-Tossou; Esaïe, Kpadonou Gbedehoue; Badou, Djigbo Félicien (Nexus Regional Dialogues Programme, 2023)
In less than one year the Niger Basin Authority, an intergovernmental body tasked with the sustainable development of the Niger waters and associated resources, passed the first ever nexus policy in a transboundary river basin, contributing to a true acceleration of change for improved water and associated development in the Niger River Basin. The guidelines were developed in close collaboration with the nine basin countries and complemented by a large capacity building program. Using the guidelines can reduce the threat of adverse impacts on the Basin’s shared water and land resources and save millions of dollars of investment funds, while meeting various Shared Vision objectives. Doing so can also help strengthen positive impacts, reduce crosssectoral constraints of single-sector solutions, and identify multisector solutions. Application of the nexus guidelines will increase the efficiency of natural resources use and support implementation and monitoring of (multipurpose) investments. If this can be achieved, the River of Rivers—thought to be the original meaning of the name Niger—will continue to enhance water, food and energy security, and environmental sustainability for generations to come. To support the application of the guidelines, the study team developed an online, simplified nexus assessment tool that is summarized in Appendix 4.